Konstruksi Makna Teroris dan Terorisme di Media Online (Analisis Wacana Theo Van Leeuwen) - Sunaryanto Sunaryanto (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Major goal of this research is to discover the meaning of terrorists and terrorism in Okezone.com and Republika.co.id. Minor goal of this research is the first to find anyone who is called terrorism by the media. Second to find any motive behind an act of terrorism according to the second version of the media discourse. This research is classified in the level of media texts and do not use the level of context. Methods of data interpretation using semiotics initiated by Theo Van Leeuwen. Conclusion of the study is that if the perpetrators of terror bombings are Muslims, then the media makes a discourse that terrorists are criminals, who are the main culprits are Muslims. Meaning terrorist generalized such that impressed that all Muslims are terrorists. Terrorism is defined by the mass media in accordance with the ideology associated with the ideology of Islam if terrorists are Moslems. If terrorists instead of people who are Muslims, then the meaning of terror and terrorism becomes ambiguous. Meaning adapted to the economic interests that accompany the online media. Motif terrorism constructed by the media is more on economic interests.